Pengaruh Sistem Pembelajaran Daring Di Masa Covid-19 Terhadap Tingkat Pemahaman Materi Pada Mahasiswa Prodi Pendidikan Bahasa Indonesia Di Universitas Muhammadiyah Bulukumba 2021 - Kaharuddin Kaharuddin; Sitti Hajar; Ridha Ichwanty Sabir (Elementary Journal : Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This study aims to determine how the level of understanding of the material in Indonesian language education study program students at the University of Muhammadiyah Bulukumba in conducting learning through online methods. The type of research used is descriptive qualitative with in-depth interviews with several informants. The focus of this research is the communication problems that arise during the implementation of online learning and the level of understanding of student learning materials carried out during the Covid-19 pandemic. The results of this study indicate that in the implementation of online learning there are many problems that cause the enthusiasm for learning and the level of student learning understanding to decrease. Internet access also has a big role in online learning. The uneven availability of the internet in Indonesia causes some students to find it difficult to access learning materials. This causes students to have difficulty understanding the learning material.